Examining Influencers Role in TikTok Shop’s Promotional Strategies and Consumer Purchases - Ronal Aprianto; Ade Famalika; Irma Idayati; Derli; Ihsan Nuril Hikam (Aptisi Transactions On Technopreneurship (ATT), 2024)
TikTok Shop, a new feature by TikTok, facilitates direct transactions within the app, representing an innovative entrepreneurship venture. This study assesses how product quality and free shipping promotions influence purchase decisions, with influencers as mediators, a key element in digital entrepreneurship. Survey- ing 352 students from PTS Lubuklinggau City through online questionnaires, the research adopted a quantitative approach using SEM-PLS analysis via Smart- PLS software. Findings indicate that product quality significantly positively affects influencers, encouraging them to endorse products, a testament to the entrepreneurship success of quality management. Similarly, free shipping pro- motions positively impact influencers, highlighting their effectiveness in influ- encer marketing and entrepreneurship marketing strategies. Importantly, product quality significantly influences consumer purchasing decisions, showcasing its critical role in sales success and entrepreneurship value creation. However, the impact of free shipping on purchase decisions, while positive, is not significant, suggesting that it alone may not drive consumer buying behavior. Influencers significantly affect purchasing decisions, directly and indirectly, demonstrating their crucial role in marketing strategies and entrepreneurship ecosystems. They enhance the effect of product quality and free shipping on consumer choices, acting as a bridge between the product features and the consumers’ decisions to buy. This study reveals the complex dynamics of influencer marketing within the TikTok Shop ecosystem, emphasizing the importance of product quality and strategic promotions in driving purchase decisions and fostering entrepreneur- ship growth.